Construction of a New Class of Generating Functions of Binary Products of Some Special Numbers and Polynomials - Boughaba, Souhila; Boussayoud, Ali; Araci, Serkan; Kerada, Mohamed; Acikgoz, Mehmet; Aracı, Serkan (UNIV NIS, 2021)
In this paper, we derive some new symmetric properties of k-Fibonacci numbers by making use of symmetrizing operator. We also give some new generating functions for the products of some special numbers such as k-Fibonacci numbers, k-Pell numbers, Jacobsthal numbers, Fibonacci polynomials and Chebyshev polynomials.
Keywords: Symmetric functions; Generating functions; k-Fibonacci numbers; k-Pell numbers; Jacobsthal numbers